The effectiveness of media in Iraqi theatre performances, the play (The Pawns) as a model (Al-Academy, 2025)
The digital revolution has become an inevitable reality that we live in, casting its shadow over various aspects of life. The theater has not been devoid of this influence, especially with the emergence of post-modern features with all its intellectual, philosophical and aesthetic visions. However, with the technological development in this context, theater professionals, directors and actors seek to establish effective relationships with the Internet and digital media, which has led to the emergence of many websites interested in theater. From here, the importance of linking culture, digital theater theory and the effectiveness of media emerged to establish a new theatrical thought that is launched within an intellectual, aesthetic and scientific system oriented towards the recipient. On this basis, the researcher formulated the title of his research (The Effectiveness of Media in Iraqi Theater Performances, The Play "Al-Bayadiq" as a Model)? The methodological framework presents the research problem and focuses on the following question: Did the effectiveness of media in Iraqi theater performances play an effective role in the theatrical performance system? The research aims to identify the effectiveness of media in Iraqi theater performances (Al-Bayadiq as a Model). The first section deals with the concept of media and its effectiveness. The second section deals with the functions of media in theatrical performances. The research procedures included the research community, samples, tools, and a descriptive analysis approach to the effectiveness of media in Iraqi theatrical performances, using "Al-Bayadiq" as a model. The results and conclusions were summarized, the most prominent of which are:The theatrical performance "Al-Bayadiq" worked to change the traditional style and differentiate it from traditional performances by employing media and its functions in the theatrical performance.The employment of media and its functions in the theatrical performance, as well as its effectiveness, had an impact on the audience, deepening their response to the overall atmosphere of media and its functions.Media and its effectiveness in the theatrical performance constituted a qualitative addition to the visions of the Iraqi director through the aesthetic and philosophical changes witnessed in the contemporary theatrical performance.The research concluded with recommendations, proposals, and a summary of the research in English